Spontaneous Regression of Osteochondroma – A Rare Phenomenon - King, Chia Kok; Haron, Juhara; Malek, Nik Fatimah Salwati Nik (International Journal of Human and Health Sciences (IJHHS), 2021)
Background: Osteochondroma is a common benign bone tumour, but its spontaneous regression is a rare occurrence. The first case was reported by Hunter in 1786. And only 30 cases were found in literature to date. Spontaneous regression of osteochondroma usually occurs in paediatric age group prior to skeletal maturation without any sequelae. The exact pathophysiology of its spontaneous regression is still not fully understood. We report a case of spontaneous regression of osteochondroma in a child after a 6-year period of follow up without needing any surgical intervention. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 372-374